1988
DOI: 10.1001/jama.1988.03720150056037
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Solvent Exposure and Glomerulonephritis

Abstract: We describe a patient who presented with renal failure after a one-year period of unprotected heavy occupational exposure to organic solvents. Renal biopsy results and serological findings were diagnostic of anti-glomerular basement membrane antibody-mediated glomerulonephritis. An analytic review of the literature revealed substantial evidence linking solvent exposure to the development of glomerulonephritis (GN), with seven of nine case-control studies demonstrating a statistically significant association. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 42 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Patients with organic solvents related nephrosis have been reported [1][3]. All patients manifest typical nephrosis with severe edema, massive non-alternative proteinuria, hypoalbuminemia and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with organic solvents related nephrosis have been reported [1][3]. All patients manifest typical nephrosis with severe edema, massive non-alternative proteinuria, hypoalbuminemia and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%
“…An Australian research 13 reported a prevalence of 36% of patients with anti-GBM disease have normal renal function. Other studies have found that 15%-35% [20][21][22][23][24] of patients with anti-GBM disease have normal renal function. All ve patients with normal renal function are alive, and the serum creatinine is less than 0.2 mmol/l in all (100%), hematuria persists in one (20%), and proteinuria > l g/day in two (40%).…”
Section: Rheumatol2015mentioning
confidence: 99%
“…A higher level of autoantibodies are described after a wide variety of chemical exposures, including chlordane (Robinson 1996), solvents (Daniell, Couser, and Rosenstock 1988;Bombassei and Kaplan 1992), chlorinated solvents (Montoya 1990), PCBs/PBBs (Safran et al 1987), organochlorine, organophosphate and other pesticides (Street 1981), formaldehyde and aliphatic amines (Brooks et al 1985), silicone (Press et al 1992;, chlordane (Ziem and McTamney 1997), chlorpyrifos (Ziem and McTamney 1997), malathion (Ziem and McTamney 1997), and formaldehyde (Tarlo and Broder 1989). A greater number of chemical-speci c antibodies has been noted after exposure to building materials in remodeling (Thrasher et al 1989).…”
Section: Petrochemical-induced Injurymentioning
confidence: 99%